2014
DOI: 10.1002/bjs.9418
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of postoperative morbidity and perioperative mortality in patients receiving neoadjuvant chemotherapy or chemoradiotherapy for resectable oesophageal and gastro-oesophageal junctional cancers

Abstract: Neither NAC nor NACR for oesophageal carcinoma increases the risk of postoperative morbidity or perioperative mortality compared with surgery alone. There was no clear difference between NAC and NACR. Care should be taken with NACR in oesophageal SCC, where an increased risk of postoperative mortality and treatment-related mortality was apparent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
137
2
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(160 citation statements)
references
References 59 publications
(139 reference statements)
9
137
2
8
Order By: Relevance
“…Esophageal cancer (EC) is one of the most malignant gastrointestinal cancers worldwide (1,2). Neoadjuvant therapy followed by surgery is the standard treatment for patients with resectable thoracic esophageal squamous cell carcinoma (ESCC) (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…Esophageal cancer (EC) is one of the most malignant gastrointestinal cancers worldwide (1,2). Neoadjuvant therapy followed by surgery is the standard treatment for patients with resectable thoracic esophageal squamous cell carcinoma (ESCC) (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…What was notable was that all of the six patients with leakage had undergone NCRT and cervical anastomosis. Some studies suggested that NCRT was a risk factor for morbidities and mortalities (19,20), while some others hold the opposed idea (21)(22)(23). A retrospective study from our center reported that cervical leakage occurred more frequently than intrathoracic leakage (23.6%, 145/615 vs. 5.0%, 101/2,023, P<0.001) (24).…”
Section: Discussionmentioning
confidence: 86%
“…1,52 At the same time, neoadjuvant chemotherapy has not been shown to increase anastomotic leak rate in esophageal surgery. [53][54][55] Although logically, one would assume there would be an association between neoadjuvant therapy and anastomotic leak, to date, there is no consensus about this relationship.…”
Section: Steroids/immune Modulatorsmentioning
confidence: 99%